Painters' paintings from Freud to Van Dyck - Robbins, Anne (National Gallery Company, 2016)
Painters have always owned the work of other artists. Exploring the collections of Freud, Matisse, Degas, Leighton, Watts, Reynolds and Van Dyck, Anne Robbins poses a fascinating question: why do artists acquire the work of other painters? She reveals how their motivations can be emotional, intellectual or tactical, and how painters’ paintings can evoke friendships, jealousies, homage, or even veneration. Casting a forensic eye over every aspect of painters’ paintings, Robbins examines how they were bought (sometimes at great personal cost), swapped, borrowed or given. She shows how artists used these pictures, extracting their technical secrets and repeatedly appropriating motifs, poses and subject matter. Some elaborated histories of art around their collections, others flaunted them to boost their own reputation. We may think we know famous painters, but this book casts an intriguing new light on their collecting habits and obsessions. There are rich, multi-layered connections between works owned and works painted: painters’ paintings are the point of departure for artists’ own creativity
Includes bibliographical references. - Published to accompany the exhibition "Painters' paintings. From Freud to Van Dyck", The National Gallery, London, 23 June - 4 September 2016
Keywords: Leighton of Stretton, Frederic Leighton -- 1830-1896; Reynolds, Joshua -- 1723-1792; Dyck, Anton van -- 1599-1641; Lawrence, Thomas -- 1769-1830; Freud, Lucian -- 1922-2011; Watts, George Frederick -- 1817-1904; Matisse, Henri -- 1869-1954; Degas, Edgar -- 1834-1917; Painters / History; Painting / Collectors and collecting / History; Geschichte; Motivation; Maler; Sammlung; Malerei; Ausstellungskatalog -- National Gallery -- 23.06.2016-04.09.2016 -- London